Research on the construction of an indicator system for physical education teaching abilities of preschool teachers - Shi, Zuozheng; Yang, Xulin; Xu, Binglong; Long, Xi (Frontiers in Psychology, 2025)
BackgroundThe purpose of this study is to construct a physical education competency index system for early childhood teachers to improve their practical ability to structure early childhood physical education programs and to promote the high quality development of early childhood physical education programs.MethodsUsing the Delphi method, a multidisciplinary expert group was formed to systematically evaluate the physical education competency index system for early childhood teachers. The consistency and stability of the physical education competency index system for preschool teachers were investigated in detail using a 5-point Likert scale.ResultsAfter two rounds of Delphi surveys, the results showed that consensus was reached on all 5 first-level indicators, 17 s-level indicators, and 54 third-level indicators included in the physical education competency indicator system for preschool teachers, and that the stability of the indicators was good. The physical education competency index system we have developed for early childhood teachers is reliable and reasonable.ConclusionThe findings of this study not only effectively enhance the physical education teaching skills of preschool teachers, but also provide a basis for the development and evaluation of structured physical education curricula for preschoolers.